Global Human Resource Management in Improving Corporate Competitiveness. - Yasman Yasman; Limgiani Limgiani (International Journal of Educational Evaluation and Policy Analysis, 2025)
Human Resource Management (HRM) has become essential to a company's success in the global marketplace in the fast-paced age of globalisation. Global HRM is an approach that takes into account global elements like market demands, labour laws, and cultural norms. Managing scattered teams, adjusting to cultural diversity, and differing labour laws are among the difficulties. Global HRM does, however, also offer advantages, such as easier access to talent from throughout the world. This journal attempts to offer useful insights for HRM practitioners and business executives in managing human resources in the age of globalisation through in-depth examination.Literature reviews serve as the data source for the qualitative and descriptive research methodology. The study's findings emphasise how crucial global human resource management is to accomplishing corporate objectives in a variety of international marketplaces. Flexibility, efficient resource management, improving cultural sensitivity, and employee participation are some of the suggested remedies. In the age of global business, companies can improve performance and accomplish their objectives by putting in place efficient HRM strategies.